The social image of drinking: mass media campaigns may inadvertently increase binge drinking - Zimmermann, Friederike; Kohlmann, Karoline; Monter, Anne; Ameis, Nina (Psychology, health & medicine, 2017)
Mass media campaigns that promote responsible drinking are rarely tested for their usefulness in reducing heavy alcohol consumption. Existing campaigns that appeal to responsible drinking while simultaneously displaying young people in social drinking situations may even have paradoxical effects. To examine such possible effects, we drew on a real-world media campaign, which we systematically modified on the basis of recent prototype research. We pilot tested questionnaires (using n = 41 participants), developed two different sets of posters in the style of an existing campaign (n = 39) and investigated their effectiveness (n = 102). In the main study, young men were randomly assigned to one of three conditions: sociable or unsociable binge drinker prototype condition or a control group. Outcome variables were intention, behavioural willingness, attitude, subjective norm, self-efficacy, prototype evaluation and prototype similarity with respect to binge drinking. Binge drinking as a habit was included to control for the fact that habitual drinking in social situations is hard to overcome and poses a particular challenge to interventions. The manipulation check showed that the experimental variation (sociable vs. unsociable drinker prototype condition) was successful. Results of the main study showed that the sociable drinker prototype condition resulted in a higher willingness and - for those with less of a habit - a higher intention to binge drink the next weekend. The unsociable drinker prototype condition had no effects. The results imply that the social components of mass media campaigns might inadvertently exacerbate binge drinking in young men. We therefore advocate against campaigns including aspects of alcohol consumption that might be positively associated with drinker prototype perception. Finally, we provide suggestions for future research.
Published online: 23 Nov 2016
Gesehen am 16.05.2018